Extraction and Purification of Flavonoids and Antiviral and Antioxidant Activities of Polygonum perfoliatum L. - Chan Zhao; Jian Xu; Yao Liu; Peng Xu; Jin Yi; Lin Feng; Yanyan Miao; Yongping Zhang (Molecules)
The aim of the present study was to optimize the process parameters for the extraction and purification of total flavonoids from Polygonum perfoliatum L., in addition to analyzing their chemical composition and evaluating their activity against varicella-zoster virus (VZV) and antioxidant activity. The optimum extraction process was determined using one-way and response surface methods with the following conditions: ethanol concentration of 82.00%, temperature of 90.29 °C, solid-to-liquid ratio of 1:32.78 g/mL, extraction time of 1.5 h, and two extractions with a yield of 14.98 ± 0.11 mg/g. Purification was then carried out using D101 macroporous resin to obtain a flavonoid purity of 43.00 ± 2.55%, which was 3.38 times higher than that of the crude extract (12.74 ± 1.04%). Further purification was carried out using a 1:9 hybrid column of macroporous resin and polyamide, and the purity of flavonoids was enhanced to 59.02 ± 2.23%, which is 1.37 times higher than that of the macroporous resin purifier (43.00 ± 2.55%) and 4.63 times higher than that of the crude extract (12.74 ± 1.04%). Seventy-nine flavonoids were identified using ultra-performance liquid chromatography-tandem high-resolution mass spectrometry (UPLC-HRMS). In addition, the purified flavonoids showed good anti-VZV and antioxidant activities. Therefore, this study can provide technical support and theoretical basis for the further development and utilization of Polygonum perfoliatum L. resources.